Strategic learning and corporate investment - Décaire, Paul H.,Wittry, Michael D. (The Ohio State University, Fisher College of Business, Charles A. Dice Center for Research in Financial Economics, 2022)
Using detailed project-level data, we document a novel mechanism through which information externalities distort investment. Firms anticipate information spillover from peers’ investment decisions and delay project exercise to learn from their peers’ outcomes. To establish a causal interpretation of our results, we exploit local exogenous variation from the 1800s that shapes the number of peers that a firm can learn from today. The strategic learning incentive is most salient for projects with uncertain profitability, when peers’ underlying assets are similar, and in environments where peers are skilled. Finally, our results suggest that the anticipation of peer information dampens aggregate investment
10.2139/ssrn.3923811
Keywords: Graue Literatur; Real options; corporate investment; strategic interactions; peer learning; his-torical data